Physiological and molecular characterization of copper and antibiotic resistance mechanisms in Pseudomonas aeruginosa strain PaD2 - JUANDY JO; DIAN ANGELICA TRYOANITA UMBU DATTA; WAHYU IRAWATI; JONATHAN SUCIONO PURNOMO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Jo J, Datta DATU, Irawati W, Purnomo JS. 2025. Physiological and molecular characterization of copper and antibiotic resistance mechanisms in Pseudomonas aeruginosa strain PaD2. Biodiversitas 26: 1526-1536. Environmental pollution by heavy metals and antibiotics promotes the growth of co-resistant bacteria that can spread multiple resistance genes. Bioremediation using indigenous bacteria from such polluted sites is a potential solution to this problem. We recently isolated Pseudomonas aeruginosa strain PaD2 from the polluted Sukolilo River in Surabaya, Indonesia, and found it to be resistant to high copper concentrations. Therefore, we investigated the resistance profiles of P. aeruginosa PaD2 to Cu and various antibiotics using physiological and molecular approaches. Antibiotic resistance was evaluated in the presence of 4 mM CuSO?, as compared to that without Cu addition, using disk diffusion and broth macrodilution assays. The whole genome of P. aeruginosa PaD2 was sequenced to identify relevant resistance genes. Pseudomonas aeruginosa PaD2 exhibits resistance to both copper and various antibiotics (e.g., cefoxitin, erythromycin or tetracycline). Interestingly, Cu exposure did not significantly alter the antibiotic resistance profiles, indicating that Cu and antibiotic resistance mechanisms were independent. Genome analysis identified genes related to efflux pumps, antibiotic inactivation, and target modification, which may explain the multidrug resistance phenotype. In conclusion, P. aeruginosa PaD2 should be further tested as a bioremediation agent for copper and antibiotic pollution.